Characterization of cutaneous microvasculature using 3D imaging: A feasibility study in a cohort of head and neck surgery patients with attention to smoking status - O.M. Alese; A.C. Wilson; K.M. Tessier; A. Loavenbruck; C. Dedeker; A.A. Lassig (JPRAS Open)
Summary: Background: This study explored a new method to characterize cutaneous microvasculature and evaluated the associations between baseline vessel characteristics and post-operative wound healing outcomes. Materials and Methods: We prospectively enrolled 17 adult patients undergoing major head and neck surgery. A full thickness cutaneous biopsy from the inferior surgical skin flap of the neck incision was obtained and processed for immunohistochemical analyses. Collagen IV antibody was immunolocalized along with secondary fluorophore-conjugated antibodies for confocal microscopy. The Vesselucida 360 software was used to morphologically characterize the cutaneous vasculature by tracing 3D sections of the collagen IV-stained vessels. Vessel structure metrics including isolated elements (individual vessel structures) and patient characteristics were evaluated for associations. Statistical analyses were performed using R version 3.6.1 and SAS version 9.4; a p-value of 0.05 was considered significant. Results: Males and prior chemotherapy patients trended toward higher isolated elements compared with females and patients without a history of chemotherapy. Vesselucida assessment results indicated that current and former smokers were found to have more tortuous vessels and irregular vessel walls than never-smokers. Isolated elements were significantly higher in patients who returned to the hospital owing to a wound complication, required long-term wound care, or had other complications. Vascular endothelial growth factor A was positively correlated with vessel endings and total surface area, whereas placental growth factor was positively correlated with isolated elements and endings. Conclusions: We described the use of Vesselucida 360 as an innovative tool to characterize cutaneous vasculature; using this tool, the increase in isolated elements was found to be associated with poorer wound healing outcomes.